Respuesta :

Answer:

Step-by-step explanation:

(x + 3)² − 5   because :

(x + 3)² − 5 = x² +6x+9 -5 =x²+6x+4

Answer:

B) [tex](x + 3)^2 - 5[/tex]

Step-by-step explanation:

the equation is: [tex]x^2 + 6x + 4[/tex]

we have an equation of the form

[tex]ax^2+bx+c[/tex]

where

[tex]a=1,b=6,c=4[/tex]

and we must complete the square to obtain a perfect square binomial,

we must add and substract the following:

[tex](\frac{b}{2a} )^2[/tex]

which is:

[tex](\frac{6}{2*1} )^2=3^2[/tex]

and then the equation becomes:

[tex]x^2 + 6x + 4+3^2-3^2[/tex]

where the terms [tex]x^2+6x+3^2[/tex] are the components of the perfect square binomial: [tex](x+3)^2[/tex]

and thus, the equation now is:

[tex](x+3)^2+4-3^2\\=(x-3)^2+4-9\\=(x+3)^2-5[/tex]

the answer is: B) [tex](x + 3)^2 - 5[/tex]